Poetry Out Loud: Two Perspectives, Overview - Richard, Julie (Maine Policy Review, 2015)
Poetry Out Loud, a national poetry recitation contest begun by the National Endowment for the Arts and the Poetry Foundation in 2006, is described from two perspectives: this short article is by the director of the Maine Arts Commission, which administers the program in Maine.
Keywords: humanities; Poetry Out Loud; Maine